A case of enzyme immunoassay validation for the determination of clenbuterol residues in bovine urine. (8th November 2007) - Cebulj-Kadunc, Nina; Cestnik, Vojteh
Using the method of standard addition, a commercial EIA for qualitative screening of clenbuterol in bovine urine was validated. The method was robust on the influence of external factors. The recovery was 167.86% and CCβ 618.86 ng/L, and should be considered by presentation of quantitative results. Due to high crossreactivity, high responses are expected in test samples, contaminated with other β-agonists. Therefore, suspicious samples must be retested with confirmatory methods, indicating which substance is actually present. The results of validation implement the expected demands, indicating the method is suitable screening procedure for determination of clenbuterol in bovine urine.